2019
DOI: 10.1111/bjd.17706
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia improves hair inductivity of dermal papilla cells via nuclearNADPHoxidase 4‐mediated reactive oxygen species generation'

Abstract: Summary Background Dermal papilla cells (DPCs) play a key role in hair regeneration and morphogenesis. Therefore, tremendous efforts have been made to promote DPC hair inductivity. Objectives The aim of this study was to investigate the mitogenic and hair inductive effects of hypoxia on DPCs and examine the underlying mechanism of hypoxia‐induced stimulation of DPCs. Methods DPCs' hair inductivity was examined under normoxia (20% O2) and hypoxia (2% O2). Results Hypoxia significantly increased the proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 50 publications
3
38
0
Order By: Relevance
“…This result is in line with a study showing the activated fibroblast-derived EVs could induce cell proliferation signaling in DP cells [43]. This could be very useful for large-scale production of DP cells in vitro for research studies and DP cells therapies [47,48], as cultured DP cells lose their ability of inducing and maintaining the HF. This also could maintain the ability of proliferation of DP cells in vivo.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result is in line with a study showing the activated fibroblast-derived EVs could induce cell proliferation signaling in DP cells [43]. This could be very useful for large-scale production of DP cells in vitro for research studies and DP cells therapies [47,48], as cultured DP cells lose their ability of inducing and maintaining the HF. This also could maintain the ability of proliferation of DP cells in vivo.…”
Section: Discussionsupporting
confidence: 87%
“…A study compared the cultured DP cells from balding and non-balding scalp and found that balding DP cells showed characteristics of senescence, including loss of proliferation [46]. Cultured DP cells lose their ability of inducing hair follicle after sub-culturing in vitro [47], showing that DP cell proliferation is essential for the morphogenesis and growth of the HF [2]. In the current study, MAC-EVs were shown to have the capacity to induce proliferation of DP cells, which was further confirmed by upregulated PCNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…The ROS generating system was further examined, and EREG increased cellular ROS level, but did not lead to ROS generation in the mitochondria of DPC (Figure ). The expression of Nox4 was high in the nucleus of DPCs, 14 and Nox4 silencing attenuated the ROS level, NOX4 expression and DPC stimulation by EREG, suggesting that EREG increased ROS generation through nuclear NOX4 expression in DPCs. It was reported that amphiregulin (AREG) and HB‐EGF have the same effect at increasing NOX1 expression in smooth muscle cells 25 .…”
Section: Discussionmentioning
confidence: 90%
“…While this seems to contradict the expected relation between the available oxygen and the ROS formation, it is also known that spheroids represent a hypoxic environment [49,50]. Thus, the oxygen levels in the highly compact DP-hMel aggregates are also likely to be below 5%O 2 and lead to the formation of ROS by an alternative mechanism [19], as it was previously demonstrated to play a key role in the stimulation of DP cells inductivity [22]. Moreover, ROS increase in the 3D-cellular aggregates may also be a consequence of the improved tyrosinase activity which is, by itself, a ROS-generating oxidative step [51,52].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies demonstrated that in cultures performed under 21%O 2 (normoxia) both HF mesenchymal (DP and dermal sheath cells) [20] and epithelial [21] populations proliferate at lower rates than when respectively cultured at 6%O 2 or 4%O 2 . Moreover, under hypoxic conditions (2%O 2 ), DP cells viability, phenotype and inductivity are improved [18,22]. Further, hMel proliferation and melanin production are also higher at 1-5%O 2 than above normoxia [23].…”
Section: Introductionmentioning
confidence: 96%